Insights into the time course of evidentiality processing in Turkish heritage speakers using a self-paced reading task - Tokaç-Scheffer, Suzan D.; Arslan, Seçkin; Nickels, Lyndsey (Frontiers in Communication, 2023)
Studies with heritage language speakers (HLS) have often used offline measurements, investigating the post-interpretive effects which emerge after processing has been completed. Relatively few studies have investigated heritage language processing using time-sensitive methods that allow the collection of evidence regarding real-time language processing rather than post-interpretive judgments. Using a self-paced-reading paradigm, we aimed to expand our understanding of HLS language processing by investigating evidentiality – the linguistic marking of information source, which is grammatically expressed in Turkish, but not in English. Participants were 54 bilingual speakers of Turkish and English: 24 HLS (English onset:0-5yrs) and 30 emigrant Turkish speakers(ES) who grew up in Turkey before emigrating to Australia (English onset=6-17yrs). Participants read sentences with evidential-marked verb forms that either matched or mismatched to the information source context. Word-by-word reading times and end-of-sentence acceptability judgment speed and accuracy were measured. The results showed that although the HLS’ responses were slower and less accurate than the ES in both reading times and end-of-sentence acceptability judgments, they showed similarities in online processing patterns. Both groups were faster at reading the mismatching sentences compared to the matching sentences; however, this pattern emerged first for the indirect condition for the ES, and only later for the direct condition and for the HLS for both evidential conditions. Only HLS read faster in the target region with the direct evidential, that is shown to be acquired earlier in the childhood, than they did for the indirect evidential, which is mastered later. In contrast, the end-of-sentence judgment data showed that while the ES group responded faster to matching direct sentences than matching indirect, this effect was missing for the HLS. Nevertheless, there were similar patterns for accuracy across evidential conditions: both groups were more accurate with the direct evidential. Overall, the self-paced-reading paradigm allowed insights into HLS' evidentiality processing above and beyond their generally slower and less accurate processing compared to the reference group. This study has provided further evidence for differences in the patterns observed using online vs. post-interpretive measures in HLS, reinforcing the importance of combining these methodologies for further understanding of HLS competence and performance.